The Kennedy girl - Thomas, Julia, 1959- (Sourcebooks Landmark, 2025)
"From esteemed author Julia Bryan Thomas comes a novel for readers who loved the fashion and glamour of The Secret Life of Mirielle West and the clandestine intrigue of The Secrets We Kept, showcasing a journey to France through the eyes of a wide-eyed American orphan who becomes embroiled in an international espionage scheme. 1960. New York, Paris and Milan fashion culture is starting to make an impression on the average American woman. When a mysterious bakery customer suddenly offers newly orphaned Mia a modeling job in Paris at the esteemed House of Rousseau, she takes a chance on it, despite it seeming too good to be true. But the job of a model goes deeper than photoshoots and runway walks, and as Mia adjusts to the Parisienne lifestyle, she soon finds herself implicated in an espionage plot run by the very fashion house she works for. As she is drawn further into national crimes and politics, Mia will soon have to decide which side of history she's really on"--